Prototype Development of Simple Boost Control Technique For Z-Source Inverter - Che Nasir, Muhamad Hakimi (IRC, 2019)
This paper explains about Z-source inverter (ZSI), which is part Z-source converter. As traditional converter such as voltage-source converter and current-source converter have their major disadvantages that can poorly effect on electrical system, Z-source converter has been chosen as the most suitable alternative. Z-source converter can be applied to all kind of conversion, which are dc-dc, dc-ac, ac-ac and ac-dc. However, this research project mainly stresses about the dc-ac or inverting part. Z-source inverter has different kind of topologies, such as Improved Z-Source Inverter (IZSI), depend on the usage and its efficiency demand. IZSI has two major advantages compared to conventional ZSI, which are the ability to compress the capacitor voltage stress and also to surpass the inrush current ability. Based on these variables, both ZSI and IZSI will be compared in simulation mode, by using Matlab/SIMULINK software. One of the methods to control the switches in ZSI and IZSI is by using simple boost control method. Using this method, it allows the any two or more legs of the switches to be short-0circuited at the same time without creating any damage to the circuit. This situation then leads to the existence of active and non-active state. In this research project, simulation of z-source inverter had been conducted and all of the result will be presented at the end of the project, in term of comparison of both ZSI and IZSI outputs using simple boost control method.